Evaluation of Food Wastes in Chlorella vulgaris Cultivation for Remazol Brilliant Blue R Biosorption - Gönül Dönmez; Sevgi Ertuğrul Karatay; Nazlıhan Tekin; Safiye Büşra Nazlı (Aquatic Sciences and Engineering)
The current study demonstrates the biosorption efficiency of Chlorella vulgaris for the removal of Remazol Brilliant Blue R (RBBR), which is often used in the textile industry. For this, optimization of microalgal growth was investigated under photoautotrophic conditions including only BG-11 medium and photoheterotrophic conditions containing 0.5 g/L of pumpkin waste, apple pomace, or glucose. Some critical parameters for RBBR biosorption onto dry C. vulgaris biomass, such as pH (2-10), initial concentration of RBBR (100-800 mg/L), biosorbent concentration (1-3 g/L), and biosorption time (0-120 min) were optimized. As a result of the study, the best growth of microalgae was determined as 0.502 g/L under photoheterotrophic cultivation condition, including 0.5 g/L of pumpkin waste sugar. The highest dye removal was calculated as 99.49% in the presence of 3 g/L microalgal biosorbent and 103.38 mg/L RBBR concentration at pH 4. These results indicate that C. vulgaris has a promising biosorbent for waste management and dye removal.